Low-threshold 2 μm InAs/InP quantum dash lasers enabled by punctuated growth - Chu, Rafael Jumar; Laryn, Tsimafei; Ahn, Dae-Hwan; Han, Jae-Hoon; Kim, HoSung; Choi, Won Jun; Jung, Daehwan (Optical Society of America, 2024)
2 pm photonics and optoelectronics is promising for potential applications such as optical communications, LiDAR, and chemical sensing. While the research on 2 pm detectors is on the rise, the development of InP-based 2 pm gain materials with 0D nanostructures is rather stalled. Here, we demonstrate low-threshold, continuous wave lasing at 2 pm wavelength from InAs quantum dash/InP lasers enabled by punctuated growth of the quantum structure. We demonstrate low threshold current densities from the 7.1 pm width ridge-waveguide lasers, with values of 657, 1183, and 1944 A/cm2 under short pulse wave (SPW), quasi-continuous wave (QCW), and continuous wave operation. The lasers also exhibited good thermal stability, with a characteristic temperature T0 of 43 K under SPW mode. The lasing spectra is centered at 1.97 pm, coinciding with the ground-state emission observed from photoluminescence studies. We believe that the InAs quantum dash/InP lasers emitting near 2 pm will be a key enabling technology for 2 pm communication and sensing.